Political Citizenship : Protection of Prisoners Political Rights by KPU Ciamis in General Elections 2024 - Pratama, Aldi Septian; Gunawan, Hendra; Gustaman, Randy Fadillah (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
This research discusses the protection of political rights of prisoners of Lapas Kelas IIB Ciamis by KPU Ciamis in General Election 2024. This study uses political citizenship to describe how the prisoners' struggle and the KPU's efforts to protect the political rights of prisoners through the four dimensions of citizenship politics. This research is a qualitative research with a case study method. The results show that there are still 17 out of 322 prisoners who are not protected by their political rights and cannot vote in elections. The struggle of prisoners includes four dimensions of citizenship politics, namely the dimensions of membership, legal status, political rights, and participation. KPU also applies new methods and improves the process of protecting the political rights of prisoners. Interaction occurred between the prisoners and the KPU and conflicts were inevitable which caused 17 prisoners to lose their political rights.